2019
DOI: 10.3389/fnins.2019.00951
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Emotional and Psychological Manifestations in Amyotrophic Lateral Sclerosis at Baseline and Overtime: A Review

Abstract: It is now well recognized that, in addition to motor impairment, amyotrophic lateral sclerosis (ALS) may cause extra-motor clinical signs and symptoms. These can include the alteration of certain cognitive functions, impaired social cognition, and changes in the perception and processing of emotions. Where these extra-motor manifestations occur in ALS, they usually do so from disease onset. In about 10% of cases, the cognitive and behavioral changes meet the diagnostic criteria for frontotemporal dementia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 177 publications
2
50
0
1
Order By: Relevance
“…Only one trial assessed the impact of the candidate drug on both neuropsychiatric symptoms and cognitive impairment. This is despite overwhelming evidence that these extramotor features are prevalent across, and impactful upon, people with ALS [5,9,20]. Whilst the impact on physical functioning and survival justifiably remain the primary objectives for clinical trials of ALS, the importance of additional assessments for neuropsychiatric and cognitive functioning needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Only one trial assessed the impact of the candidate drug on both neuropsychiatric symptoms and cognitive impairment. This is despite overwhelming evidence that these extramotor features are prevalent across, and impactful upon, people with ALS [5,9,20]. Whilst the impact on physical functioning and survival justifiably remain the primary objectives for clinical trials of ALS, the importance of additional assessments for neuropsychiatric and cognitive functioning needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…ALS is marked by progressive degeneration of upper and lower motor neurons while MS is characterized by demyelination due to an autoimmune response. Although ALS and MS have been traditionally viewed as diseases of the motor system, cognitive impairment also occurs in these pathologies (Chiaravalloti and DeLuca, 2008 ; Benbrika et al, 2019 ). It has been suggested that VIP and PACAP may contribute to ALS and MS non-motor symptomatology (Staines, 2008 ).…”
Section: Pacap and Vip Promote Cognitive Function In Neurodegenerativmentioning
confidence: 99%
“…The disease timeline is still a matter of debate. Longitudinal studies on the cognitive decline over time in ALS are still missing to the best of our knowledge; however, some cross-sectional studies have suggested poorer cognitive performance in the advanced stages of the disease [ 12 ]. It is not clear whether cognitive impairment in ALS (if it occurs) worsens in line with a physical disability.…”
Section: Clinical Manifestations Of Als-ftsdmentioning
confidence: 99%